Jurnal Review: Analisis Modifikasi Komposisi Substrat Limbah Cair Tahu Pada Pembuatan Biogas Menggunakan Metode Anaerob - Puput Eka Suryani (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2022)
Based on data from the Central Statistics Agency, the average consumption of tofu per capita continues to increase. The annual production is estimated to reach more than 2.56 million tons every year from the total tofu industry of 84 thousand. The abundance of tofu liquid waste can be used as raw material for biogas production. Biogas is an efficient method that can be used as two alternatives at once, namely to prevent environmental pollution as well as an effort to create new and renewable energy. The main objective in this analysis is to find the ideal composition for tofu wastewater treatment using the anaerobic digestion method, in order to obtain optimum biogas production. In analyzing the level of effectiveness of the modification of the mixing of tofu waste raw materials with several other materials, normal condition data is used which is used as reference data in determining whether the modified conditions are more effective or not more effective in terms of the volume of biogas produced. There are 9 samples that use volume data as a comparison of data from one sample to another. Under normal conditions without modification, tofu liquid waste with a slurry volume of 75 L can produce a biogas volume of 4.36 L with a resulting pressure of 0.12 kg/m2. From some of the data compared, the raw materials from tofu liquid waste are added with cow dung, vinasse, rumen, and yeast waste. Based on the comparison of the results of biogas produced, it can be said that the addition of cow rumen is more effective than other modifications because it increases biogas productivity by approximately 26%, and with the addition of cow rumen it can increase productivity by approximately 41%.